2005
DOI: 10.7202/009834ar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of faba beans for resistance to sclerotinia stem rot caused by Sclerotinia trifoliorum

Abstract: Sclerotinia stem rot, a fungal disease caused by Sclerotinia trifoliorum, is often a serious problem in faba beans (Vicia faba). The levels of resistance to sclerotinia stem rot were evaluated in 23 faba bean cultivars originating from various European countries, 18 cultivars from ICARDA, five cultivars from Canada, 58 populations originating from various provinces of Greece, and five V. narbonensis populations. Evaluation was done under controlled conditions following artificial inoculation with carrot root p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similar findings were found on the evaluation of plant introductions of Phaseolus spp. for resistance to white mold and the evaluation of fava beans for resistance to sclerotinia stem rot caused by Sclerotinia trifoliorum, respectively [ 53 , 54 ]. The virulence of isolates was positively correlated with colony diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were found on the evaluation of plant introductions of Phaseolus spp. for resistance to white mold and the evaluation of fava beans for resistance to sclerotinia stem rot caused by Sclerotinia trifoliorum, respectively [ 53 , 54 ]. The virulence of isolates was positively correlated with colony diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Only 14 percent of the cultivars were partially resistant to the most virulent isolate, and only one genotype, WB-1402, was resistant. It was previously reported that only 6.5 percent of dry bean cultivars of the evaluated cultivars were partially resistant, whereas more than 15 percent of the fava bean cultivars were resistant to S. trifoliorum [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%